Advanced Pulse Laser Machining Technology - Krüger, Jörg; Bonse, Jörn (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is the printed edition of the Special Issue published in Materials. The reprint provides an overview on current international research activities in the field of advanced pulse laser machining technology. It covers fundamental and applied aspects and collects contributions of renowned scientists from academics and industries working in the fields of laser processing, materials science, physics, chemistry, and engineering in order to foster the current knowledge and present new ideas for future applications and new technologies.